2018
DOI: 10.3889/oamjms.2018.177
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Osteoporosis among Saudi Physicians and Nurses: A Cross-Sectional Study

Abstract: AIM:We aimed to evaluate the awareness and knowledge of osteoporosis in a sample of 141 health professionals.MATERIALS AND METHODS:A group of 141 health professionals (medical, surgical, primary health care and nursing departments) were enrolled in this cross-sectional study in the period from August 2017 to November 2017. The participants completed a questionnaire composed of 19 questions about osteoporosis which covering the main domains of knowledge on osteoporosis. Each correct answer carried 1 point where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
4
10
1
1
Order By: Relevance
“…With respect to osteoporosis severity, according to the WHO classification, any BMD of T-score < −2.5 with a fragility fracture is considered severe osteoporosis [ 3 ]. In the current study, we reported 28 patients (13.5%) with fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to osteoporosis severity, according to the WHO classification, any BMD of T-score < −2.5 with a fragility fracture is considered severe osteoporosis [ 3 ]. In the current study, we reported 28 patients (13.5%) with fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is one of the significant global health concerns with 200 million cases reported worldwide [ 2 ]. After heart disease, osteoporosis is considered the most important health issue in developed countries [ 3 ] associated with high rates of morbidity and mortality with marked social and financial impact [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than two-thirds of the study participants believed that they would have osteoporosis later on in their lifetime. Among healthcare workers, a study by Alghamdi et al (23) showed that most healthcare workers in their investigation were assessed to have high and adequate knowledge scores of osteoporosis. Among female medical students in the Al-Ahsa region, Utkarsh et al (41)reported that only 2.3% of the study population had good knowledge scores, and 32.2% and 65.15 had poor and satisfactory levels of knowledge of osteoporosis, respectively, and therefore, the level of knowledge was considered low in this study when compared to international investigations.…”
Section: Journal Of Healthcare Sciencesmentioning
confidence: 99%
“…5 Slične studije u svetu su, za razliku od naših prilika, veoma brojne i uključile su raznovrsne subpopulacije stanovništva kao što su adolescenti i osobe mladjeg uzrasta, žene i muškarce srednje životne dobi kao i zdravstvene profesionalce -lekare i medicinske sestre. [6][7][8][9] Zato je cilj ove studije bio da korišćenjem validnog instrumenta procene kod žena u postmenopauzi ustanovi stepen znanja o značaju, merama prevencije i terapiji osteporoze u našoj sredini. Imajući u vidu oskudnost podataka iz domaćih istraživanja, očekuje se da će rezultati biti od koristi radi pouzdanijeg planiranja odgovarajućih mera u oblasti preventivne zdravstvene zaštite.…”
Section: Originalni Naučni Rad / Original Scientific Article Uvodunclassified